Pengaruh Disiplin Kerja Dan Motivasi Kerja Terhadap Kinerja Karyawan Pada PT Warna Indah Sentosa Jakarta Selatan - Muhammad Fadilah Akbar; Endang Puji Astutik (JURNAL ILMIAH NUSANTARA, 2024)
This study aims to examine the effect of work discipline and work motivation on employee performance partially and simultaneously at PT Warna Indah Sentosa , South Jakarta. This research method uses quantitative analysis methods associative method through quantitative approach, using 109 respondents. The sampling method used in this study was the slovin sampling technique. Data analysis processing techniques used descriptive analysis, classical assumption test, regression test, correlation test, coefficient of determination test, and hypothesis testing. Work discipline and motivation have a simultaneous effect on employee performance with the regression equation Y = 0.690+0.506X1 + 0.0423X2. The correlation coefficient value is 0.831, meaning that the independent variable and the dependent variable have a very strong relationship with a simultaneous determination or influence coefficient of 69,1,5% while the remaining 31,9% is influenced by other factors. The results of the partial test of Work Discipline on employee performance show a t value of 4.748 > t table 1.65936 with a significant level of 0.000 < 0.05. Thus, it can be concluded that partially work discipline has a significant effect on employee performance. The results of the partial test of Work Motivation on employee performance show a t value of 5.275 > t table 1.659 with a significant level of 0.000 < 0.05. Thus, it can be concluded that partially work Motivation has a significant effect on employee performance. The results of the F test have a probability of 0.000 < 0.05 or the value of Fcount 118,470 > Ftable 2.69. Thus it can be concluded that simultaneously work discipline and motivation have a significant effect on employee performance.